PKM PENGENALAN DASAR-DASAR AKUNTANSI SEBAGAI ALAT BANTU MENYUSUN LAPORAN KEUANGAN (Usaha Mikro Kecil Menengah/ UMKM): PKM AKUNTANSI - Wyati Saddewisasi; Djoko Santoso; Indarto (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this community service is to provide training and let the trainees understand the process of preparing financial reports with the accounting system. The benefits of training that MSME entrepreneurs and participants can take are 1) Making accounting-based financial reports, 2) The possibility of participants being able to transmit their knowledge to MSME business owners who do not take part in the training, 3) Giving information about basic accounting knowledge which can be applied to the financial application reports with computer-based software, 4) Skills in making financial reports are increasing, 5) It is easy to enter financial data with accounting-based software.